On how people deal with industrialized and non-industrialized food: A theoretical analysis - Amorim, Alessandra; Laurindo, João Borges; Sobral, Paulo José do Amaral (Frontiers in Nutrition, 2022)
“Canned, frozen, processed, ultra-processed, functional” etc. Two hundred years after the beginning of the food industry, industrialized food has evolved with many labels. Every person in the world eats and has different experiences with food that are connected to culture and social relationships which permeate our daily lives in many kinds of situations. Food evokes feelings, beliefs, desires, and moral values. For many people, food not only satisfies hunger and sustains life, but it also brings a delicious pleasure that is with their history, culture, and ancestry. Today's food industry pushes products through its marketing, which promotes a plethora of claims that have now trended proportionally with neophobic dimensions. In reality, the general public lacks objective knowledge about the complex science of modern food technology because of its low transparency, and this has resulted in the appearance of misleading ideas that can prejudice the correct analysis of food values. Given this, education about food is an urgent need. Notably, food scientists, technologists, and engineers must look at eaters through the prism of consumers who are human beings in all their rich social/anthropological diversity. The objective of this article is to explore the elemental anthropologic aspects of foods and how they can affect consumer's trust in the food industry's role.